Economic growth and social conditions of the population considered poor or more vulnerable in Peru - Gomero Gonzales, Nicko Alberto (2023)
Objective: Determine the relation between economic growth and the indicators of extreme poverty in Peru. Method: The research was descriptive, correlational, applicative with a non-experimental design; in addition, the Pearson coefficient was applied to determine the degree and type of relation, and the information was obtained from the National Institute of Statistics and Informatics for the period 2010-2021. The condition of poverty and extreme poverty materialized in social indicators, which were contrasted to the economic growth represented by the GDP per capita. Likewise, Results: Despite the economic growth evidenced in Peru in the last decade, the persistence of social indicators that are results of poverty or highly vulnerable populations is still observed. Conclusion: By contrasting the GDP per capita with technological and social indicators, it is determined that this economic indicator is positively related to technological inclusion, family income, use of the combustion system and water supply within the population of greater social vulnerability; however, these results did not lead to the closure of gaps that are structurally evident among those living under extreme poverty.